TLRs as a Promise Target Along With Immune Checkpoint Against Gastric Cancer - Cui, Lin; Wang, Xiuqing; Zhang, Dekai (Frontiers in Cell and Developmental Biology, 2021)
Gastric cancer (GC) is one of the most common cancers in the world, and the incidence of gastric cancer in Asia appears to increase in recent years. Although there is a lot of improvement in treatment approaches, the prognosis of GC is poor. So it is urgent to search for a novel and more effective treatment to improve the survival rate of patients. Both innate immunity and adaptive immunity are important in cancer. In the innate immune system, pattern recognition receptors (PRRs) activate immune responses by recognizing pathogen-associated molecular patterns (PAMPs) and damage-associated molecular patterns (DAMPs). Toll-like receptors (TLRs) are a class of pattern recognition receptors (PRRs). Many studies have reported that TLRs are involved in the occurrence, development, and treatment of GC. Therefore, TLRs are potential targets for immunotherapy to gastric cancer. However, gastric cancer is a heterogeneous disorder, and TLRs function in GC is complex. TLRs agonists can be potentially used not only as therapeutic agents to treat gastric cancer but also as adjuvants in conjunction with other immunotherapies. They might provide a promising new target for GC treatment. In the review, we sort out the mechanism of TLRs involved in tumor immunity and summarize the current progress in TLRs-based therapeutic approaches and other immunotherapies in the treatment of GC.